University Wellness Program—A Pedagogic Innovation to Nudge Wellness and Sustainability Among Students - Venkatasubramanian, Padma (Frontiers in Public Health, 2022)
Anthropocentric activities have induced climate change, threatened planetary health, and harmed human health and wellness. The changing lifestyles, dietary patterns and digital obsession have affected the mental and physical health, particularly of the youth. University campuses reflect the challenges faced by the society at large and therefore make for an ideal ecosystem to initiate positive changes toward wellness and sustainability. The energy of ~200 million university students globally is largely unleveraged for facing these challenges. Values of empathy and sustainable living are crucial to be inculcated, alongside technical and managerial skills for leading the mass transformation. This article describes a novel pedagogic approach called the University Wellness Program (UWP). The aim of UWP is to equip students with technical and leadership skills to achieve wellness and campus sustainability. That is, UWP is a platform that facilitates the students to design and implement multi-disciplinary projects that address campus related challenges. In the process, they acquire the necessary soft and technical skills to solve real-life problems. The durability of UWP is secured since the projects and activities are explicitly linked to existing curricula and evaluation system of the university. The strategy and framework adopted, and the early experiences of implementing UWP are shared. UWP is amenable for replication globally and has the potential to create change-makers.